L'epistemologia pedagogica oggi - Franco Cambi (Firenze University Press, 2009)
The Author thinks again to the historical process of pedagogy emancipation. It's a reflection about the scientific birth of pedagogy and the Author offers a question: what is the situation of epistemological research today? We can not forget that new technologies impose a new way of reflection today.